Thermal desorption behavior and binding properties of DNA bases and nucleosides on gold - Demers, Linette M. (2012)
A comparison of the binding of DNA bases (adenine, cytosine, guanine, and thymine) and nucleosides (2‘deoxyadenosine, 2‘deoxycytidine, 2‘deoxyguanosine, and thymidine) to gold thin films is presented. Desorption of monolayer/submonolayer and multilayer films of the adsorbates on gold studied via temperature-programmed desorption (TPD) and reflection−absorption infrared (RAIR) spectroscopy reveals that there are major differences in the binding affinities of the different bases to gold, for example, thymine ΔHdes = 111 ± 2 kJ/mol compared to guanine ΔHdes = 146 ± 2 kJ/mol. The differences can be rationalized by molecular structures of the bases and their binding modes to gold surfaces deduced from IR data. Similar trends in desorption energies, shifted to lower desorption energy by more than 10 kJ/mol, are observed for deoxynucleoside layers on gold thin films.